The High Value Healthcare Collaborative: Observational Analyses of Care Episodes for Hip and Knee Arthroplasty Surgery. - Weeks, Bill; Schoellkopf, William J.; Sorensen, Lyle S.; Masica, Andrew L.; Nesse, Robert E.; Weinstein, James (Journal of Arthroplasty, 2017)
Abstract Background Broader use of value-based reimbursement models will require providers to transparently demonstrate health care value. We sought to determine and report cost and quality data for episodes of hip and knee arthroplasty surgery among 13 members of the High Value Healthcare Collaborative (HVHC), a consortium of health care systems interested in improving health care value. Methods We conducted a retrospective, cross-sectional observational cohort study of 30-day episodes of care for hip and knee arthroplasty in fee-for-service Medicare beneficiaries aged 65 or older who had hip or knee osteoarthritis and used 1 of 13 HVHC member systems for uncomplicated primary hip arthroplasty (N = 8853) or knee arthroplasty (N = 16,434), respectively, in 2012 or 2013. At the system level, we calculated: per-capita utilization rates; postoperative complication rates; standardized total, acute, and postacute care Medicare expenditures for 30-day episodes of care; and the modeled impact of reducing episode expenditures or per-capita utilization rates. Results Adjusted per-capita utilization rates varied across HVHC systems and postacute care reimbursements varied more than 3-fold for both types of arthroplasty in both years. Regression analysis confirmed that total episode and postacute care reimbursements significantly differed across HVHC members after considering patient demographic differences. Potential Medicare cost savings were greatest for knee arthroplasty surgery and when lower total reimbursement targets were achieved. Conclusion The substantial variation that we found offers opportunities for learning and collaboration to collectively improve outcomes, reduce costs, and enhance value. Ceteris paribus, reducing per-episode reimbursements would achieve greater Medicare cost savings than reducing per-capita rates.